An efficient enzyme-triggered controlled release system for colon-targeted oral delivery to combat dextran sodium sulfate (DSS)-induced colitis in mice - Shangyong Li; Mengfei Jin; Yanhong Wu; Samil Jung; Dandan Li; Ningning He; Myeong-sok Lee (Taylor & Francis Group, 2021)
Oral route colon-targeted drug delivery systems (CDDSs) are desirable for the treatment of ulcerative colitis (UC). However, CDDSs are challenging owing to the physiological and anatomical barriers associated with the gastrointestinal tract (GIT). In this study, we developed an effective enzyme-triggered controlled release system using curcumin-cyclodextrin (CD-Cur) inclusion complex as core and low molecular weight chitosan and unsaturated alginate resulting nanoparticles (CANPs) as shell. The formed CD-Cur-CANPs showed a narrow particle-size distribution and a compact structure. In vitro drug release determination indicated that CD-Cur-CANPs showed pH-sensitive and α-amylase-responsive release characteristics. Furthermore, in vivo experiments demonstrated that oral administration of CD-Cur-CANPs had an efficient therapeutic efficacy, strong colonic biodistribution and accumulation, rapid macrophage uptake, promoted colonic epithelial barrier integrity and modulated production of inflammatory cytokines, reshaped the gut microbiota in mice with dextran sodium sulfate (DSS)-induced colitis. Taken together, our synthetic CD-Cur-CANPs are a promising synergistic colon-targeted approach for UC treatment.